Impact of Recreational Fishery on the Formal Danish Economy - Eva Roth; Susanne Jensen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2003)
This paper presents estimates of the economic impact of recreational fisheries on the formal economy of Denmark. It utilises primary data from a CVM (con-tingent valuation method)-mail survey conducted in 1999 in Denmark, Norway, Finland, Sweden and Iceland. The sample used in this paper covers 546 Danish respondents (recreational fishermen only). The questions on expenditure were asked in order to jog the memory of the respondents prior to the CVM questions in the form of willingness to pay questions. The annual mean amount spent on recreational fishery was estimated to be 1.170 DKK in national currency and the aggregate Danish expenditure was estimated to be 517 million DKK. The expenditure estimates from the original survey distributed on expenditure cate-gories were used as the starting point of this study. The estimation of the economic impact was done from the demand side using the Danish input-output tables. In the model each known expenditure category from the survey was allocated to a similar commodity group posting in the in-put output model nomenclature. As a result, the impact of expenditure on rec-reational fisheries activities on employment, import, indirect taxes and income was calculated.
Keywords: 330; Fischereisport; Dänemark; Makroökonomischer Einfluss